Multicystic Lesion in Jaws: A Rare Case Report on Gorlin-Goltz Syndrome - Acharya, Pradeep; Dongol, Ashok; Yadav, Anjani Kumar; Mahato, Vivek kumar; Sah, Rishikesh Pratap; Jaisani, Mehul R (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Gorlin-Goltz syndrome is an uncommon autosomal dominant inherited disorder, which is characterized by multiple odontogenickeratocysts (OKC) and basal cell carcinomas, skeletal, dental, ophthalmic and neurological abnormalities. Material and Methods: Thirteen years old male patient came with swelling of left maxilla obliterating buccal vestibule with pus discharge for 1 month. The orthopantomograph and computed tomography scan demonstrated multiple lytic lesions in maxilla and mandible. Incisional biopsy was suggestive of odontogenickeratocyst (OKC). Besides multiple OKCs; bifid ribs, palmer pits and hypertelorism were present supporting for the diagnosis as Gorlin-Goltz Syndrome. Results: The classical treatment of KCOT with enucleation with curettage or resection would have resulted in significant morbidity. Therefore we first decompressed and then enucleated the cysts. Conclusion: Gorlin-Goltz syndrome is a rare entity and the multiple KCOT can be managed with decompression followed by enucleation. Janaki Medical College Journal of Medical Sciences (2017) Vol. 5(2): 46-50